‘New’ support service – selected issues and an attempt to evaluate the regulation - Borski, Maciej; Rogacka-Łukasik, Anna (Ius Novum, 2024)
On 1 January 2024, the Act of 7 July 2023 on support benefits came into effect, introducing a new type of benefit, the support benefit. This publication aims to present the essence of the newly introduced support benefit and to attempt an evaluation of the adopted regulations. The authors also indicate the necessary directions for changes in the support system for people with disabilities, with the main goal being the empowerment of people with disabilities.